2013
DOI: 10.1111/1574-6941.12183
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities in flowback water impoundments from hydraulic fracturing for recovery of shale gas

Abstract: Hydraulic fracturing for natural gas extraction from shale produces waste brine known as flowback that is impounded at the surface prior to reuse and/or disposal. During impoundment, microbial activity can alter the fate of metals including radionuclides, give rise to odorous compounds, and result in biocorrosion that complicates water and waste management and increases production costs. Here, we describe the microbial ecology at multiple depths of three flowback impoundments from the Marcellus shale that were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 69 publications
5
85
3
Order By: Relevance
“…Halanaerobium-related sequences were also detected in PW from Barnett Shale, TX and Marcellus Shale gas wells (Davis et al, 2012;Struchtemeyer and Elshahed, 2012;Murali Mohan et al, 2013a, 2013bStrong et al, 2013;Cluff et al, 2014). However, the viability of Halanaerobium species in the previous Marcellus Shale studies was not demonstrated.…”
Section: Pw Microbiologymentioning
confidence: 89%
See 1 more Smart Citation
“…Halanaerobium-related sequences were also detected in PW from Barnett Shale, TX and Marcellus Shale gas wells (Davis et al, 2012;Struchtemeyer and Elshahed, 2012;Murali Mohan et al, 2013a, 2013bStrong et al, 2013;Cluff et al, 2014). However, the viability of Halanaerobium species in the previous Marcellus Shale studies was not demonstrated.…”
Section: Pw Microbiologymentioning
confidence: 89%
“…Recent work shows that microbial populations change during production, with different community compositions present in pre-fracturing fluids compared to PW recovered over the lifetime of production (Struchtemeyer et al, 2011;Struchtemeyer and Elshahed, 2012;Murali Mohan et al, 2013a, 2013bStrong et al, 2013;Cluff et al, 2014). In the Marcellus Shale, communities shifted during production toward halophilic and hydrocarbon-degrading lineages (Murali Mohan et al, 2013a;Strong et al, 2013;Cluff et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Recent research is beginning to define the microbial community structure of injected and flowback waters associated with hydraulic fracturing. [21][22] In Pennsylvania alone, it has been estimated that over six billion liters of wastewater have already been generated, [23] and the mismanagement of produced flowback waters is the significant threat to our water resources. [24] Frackwater has the potential to reach the stream through leaking equipment (waste-water hoses) and impoundments (evaporation pits and holding ponds/ tanks), lateral blowouts and seepage, as well as backflow into the wellhead.…”
Section: Introductionmentioning
confidence: 99%
“…Further, there are no existing studies investigating the potential effects of fracking on aquatic microbial communities. While some limited metagenomic analyses of fracturing fluids and flowback waters have identified potential microbial contaminants of wells and associated infrastructure (Struchtemeyer et al, 2011; Murali Mohan et al, 2013; Wuchter et al, 2013), nothing is currently known about the impacts of fracking on surrounding environmental microbial communities. In this study, we applied microbial community analysis to headwater stream ecosystems with different histories of fracking, specifically focusing on differences between sites with no fracking activity and those with activity.…”
Section: Introductionmentioning
confidence: 99%